Nutrient composition of Parkia biglobosa pulp, raw and fermented seeds: a systematic review - Termote, Céline; Odongo, Nicanor Obiero; Dreyer, Bettina Staeubli; Guissou, Bénédicte; Parkouda, Charles; Vinceti, Barbara (Informa UK Limited, 2022)
There is increasing evidence that nutrient differences observed among crop varieties or animal breeds belonging to the same species are sometimes greater than differences between species. Parkia biglobosa is an important tree species that provides edible products and income to rural households in West Africa. To better understand intra-species nutrient variability of P. biglobosa edible products, a review on the nutrient content of its pulp and seeds (raw and fermented) was conducted. Google scholar and the keywords “P. biglobosa” AND “nutrition” were used to screen the available literature from 1980 onwards, and the Zotero software was used to manage references. A step-wise assessment of titles, abstracts and full papers, led to a selection of 69 papers from which data were retrieved following FAO INFOODS guidelines. After data harmonization and quality checks, 42 papers were retained and used to extract data to populate a nutrient database. Despite an apparent abundance of nutrient analyses focused on P. biglobosa’s edible products, the quality of data available was poor and very few authors presented additional information, such as soil characteristics, climate, maturity at harvest, etc. that could influence the nutritional content of the products. Many data gaps remain. The present study will stimulate further investigations into nutrient composition of P. biglobosa products and ultimately will contribute to selecting nutritionally “+” trees for multiplication and/or domestication of the species.